Konspirator Konarski ponownie zakonspirowany. Szyfr zegarmistrzowski w Interesujących mężczyznach Leskowa - Zieliński, Jan (Załącznik Kulturoznawczy, 2019)
The starting point is Interesting Men, a novel by Russian prose writer Nikolai Leskov, in which the motif of 18th-century English inventor Graham’s clocks plays an important role. The novel contains a quotation in Polish thas is attributed by Leskow to Zygmunt Krasiński, but in fact it comes from a poem by Szymon Konarski, a Polish conspirator, who was shot in 1839. By profession, Konarski was a watchmaker specializing in the so-called Graham’s escapements. The article puts forward a hypothesis that Leskov knew the biography of the victim and wanted to commemorate his fate in his novel, omitting the tsarist censorship.